Manufacturing method of iron oxide magnetic powder

By using economical alkali metal silicate as the silicon source of silicon oxide coating and controlling pH value and alkali metal content, the high cost problems in the prior art are solved, and the generation of α phase is effectively reduced when producing ε iron oxides, and the performance and application range of the product are improved.

JP7659408B2Active Publication Date: 2025-04-09DOWA ELECTRONICS MATERIALS CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2021035426
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-05
Publication Date
2025-04-09
Estimated Expiration
2041-03-05

AI Technical Summary

Technical Problem

The prior art uses high-cost alkoxysilane as the silicon source for silicon oxide coatings, resulting in increased costs in the production of ε iron oxides, limiting its practical application.

Method used

A relatively economical alkali metal silicate is used as the silicon source for the silicon oxide coating, and the alkali metal content is reduced by controlling the pH value and concentration of the alkali metal silicate to reduce the formation of the alpha phase.

Benefits of technology

When using alkali metal silicate as the silicon source, it can effectively reduce the formation of α phase in ε-type iron oxide, and improve the performance and application range of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659408000003
    Figure 0007659408000003
  • Figure 0007659408000001
    Figure 0007659408000001
  • Figure 0007659408000002
    Figure 0007659408000002
Patent Text Reader

Abstract

To provide a method for manufacturing iron-based oxide magnetic powder which can suppress production of an α phase that is a different phase even when an alkali metal silicate is used as a silicon source of a silicon oxide covering layer of a precursor, in manufacture of ε type iron-based oxide magnetic powder.SOLUTION: A method for manufacturing iron-based oxide magnetic powder includes: a neutralization step of adding alkali to a solution containing metallic ions partially substituting trivalent Fe ions and Fe sites, and obtaining an iron oxyhydroxide dispersion liquid obtained by substituting the part of the Fe sites with other metal element; a silicon oxide gel covering step of adding an alkali metal silicate to the dispersion liquid obtained in the neutralization step, and obtaining an iron oxyhydroxide which is covered with a silicon oxide gel and obtained by substituting the part of the Fe sites with other metal element; and a washing step of washing a silicon oxide gel covering substitution type iron oxyhydroxide obtained in the covering step, and reducing an amount of alkali metal contained in the substitution type iron oxyhydroxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing iron-based oxide magnetic powder (hereinafter referred to as substituted iron-based oxide magnetic powder) consisting of particles of ε-iron oxide in which part of the Fe sites has been substituted with other metal elements and which is suitable for high-density magnetic recording media, radio wave absorbers, etc., in which a silicon oxide gel derived from an alkali metal silicate is used as a silicon oxide gel that coats the iron oxyhydroxide in which part of the Fe sites has been substituted with other metal elements (hereinafter referred to as substituted iron oxyhydroxide), which serves as a precursor of the substituted iron-based oxide magnetic powder. In this specification, iron-based oxides in which part of the Fe sites of ε-Fe2O3 are substituted with other metal elements may be referred to as ε-type iron-based oxides, and substitutional α-iron oxides having the same crystal system as α-Fe2O3 may be referred to as α-type iron-based oxides. [Background technology]

[0002] ε-Fe2O3 is an extremely rare phase among iron oxides, but nanometer-sized particles have a thermal conductivity of 20 kOe (1.59 × 10 6 Since ε-Fe2O3 exhibits a huge coercive force (Hc) of about 10 ... On the other hand, since the magnetic particles of ε-type iron oxides are extremely fine, in order to improve environmental resistance and thermal stability, it has been considered to replace part of the Fe site of ε-Fe2O3 with other metals with excellent heat resistance. x B y Fe 2-x-y O3 or ε-A x By C z Fe 2-x-y-z Various partial substitution products of ε-Fe2O3, which are excellent in environmental resistance and thermal stability, have been proposed (Patent Document 3), and are represented by A=Co, Ni, Mn, Zn, or other divalent metal element, B=Ti, or other tetravalent metal element, and C=In, Ga, Al, or other trivalent metal element (Patent Document 4). In addition, Patent Document 4 discloses a method for reducing the heterogeneous α-phase contained in ε-type iron-based oxides. Since ε-Fe2O3 and ε-type iron oxides are not thermodynamically stable phases, they are usually obtained by coating their precursor oxyhydroxide with silicon oxide and then firing it. The so-called sol-gel method is generally used as a method for coating silicon oxide. When using the sol-gel method, the silicon source is a hydrolyzable organic silicon compound, and the precursor is coated with the hydrolysis product, which is then heated to dehydrate the precursor oxyhydroxide, thereby obtaining ε-type iron oxide. The above-mentioned Patent Documents 1 to 4 disclose methods for producing ε-Fe2O3 or ε-type iron-based oxides using fine crystals of iron oxyhydroxide or iron oxyhydroxide containing a substitution element produced by a liquid phase method as a precursor. As liquid phase methods, a reverse micelle method using an organic solvent as a reaction medium and a method using only an aqueous solution as a reaction medium are disclosed, but as an example of a silicon oxide coating method, only a sol-gel method using an alkoxysilane as a silicon source is disclosed. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2008-174405 A [Patent Document 2] International Publication No. 2008 / 029861 [Patent Document 3] International Publication No. 2008 / 149785 [Patent Document 4] JP 2016-130208 A [Non-patent literature]

[0004] [Non-Patent Document 1] A. Namai, M. Yoshikiyo, K. Yamada, S. Sakurai, T. Goto, T. Yoshida, T. Miyazaki, M. Nakajima, T. Suemoto, H. Tokoro and S. Ohkoshi, Nature Communications, 3, 1035 / 1-6(2012) Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, by using an alkoxysilane such as tetraethoxysilane as a silicon source for applying a silicon oxide coating, it is possible to efficiently produce ε-type iron oxide with a low content of α-phase, which is a heterophase relative to the ε-phase. However, since alkoxysilanes are expensive, they increase the production cost of ε-type iron oxide, which limits the applications of ε-type iron oxide in practical use. Therefore, in order to increase the versatility of ε-type iron oxide, it has been desired to reduce the production cost by using a silicon source cheaper than alkoxysilanes for the silicon oxide coating. As a candidate for an inexpensive silicon source, it is considered to use an alkali metal silicate. Paragraph 0022 of Patent Document 1 and paragraph 0045 of Patent Document 4 mention the possibility of using sodium silicate (water glass), which is a type of alkali metal silicate, as a silicon source. However, as described above, there is no example in which an alkali metal silicate is used in the production of ε-type iron oxide. The inventors discovered that when an inexpensive alkali metal silicate is simply used instead of an alkoxysilane as a silicon source in the production of ε-type iron oxide, only iron oxide with a large content of α-type iron oxide is obtained, but that the content of the α-phase in the obtained substitutional ε-iron oxide can be reduced by reducing the content of the alkali metal in the silicon oxide coating, and filed this technology as Japanese Patent Application No. 2020-047808. The ε-type iron oxide obtained by this invention has an α-type iron oxide content of about 6.5% to 21%, which is lower than the content of α-type iron oxide when compared to the case where an alkali metal silicate is simply used as a silicon source. However, considering practical application, a further reduction in the content is required. Therefore, an object of the present invention is to provide a method for producing iron-based oxide magnetic powder that can further suppress the generation of the heterogeneous α-phase even when an alkali metal silicate is used as a silicon source. [Means for solving the problem]

[0006] The present inventors conducted extensive research and found that in a method for producing an iron-based oxide magnetic powder consisting of particles of ε-iron oxide in which a portion of the Fe site is substituted with another metal element (hereinafter referred to as substituted ε-iron oxide), when an alkali metal silicate is used as a silicon source for coating the precursor oxyhydroxide in which a portion of the Fe site is substituted with another metal element or a mixture of oxyhydroxide and a hydroxide of a substitution element (hereinafter referred to as substituted ε-iron oxide), with silicon oxide, the content of α-phase in the finally obtained substituted ε-iron oxide changes when the pH is changed when the alkali metal silicate is added to the reaction system. In addition, as disclosed in Japanese Patent Application No. 2020-047808, the content of α-phase in the obtained substituted ε-iron oxide can be reduced by reducing the content of alkali metal in the substituted ε-iron oxide coated with silicon oxide gel (hereinafter referred to as silicon oxide gel-coated substituted ε-iron oxide). Based on the above findings, the present inventors have completed the present invention described below.

[0007] In order to solve the above problems, the present invention provides [1] There is provided a method for producing an iron-based oxide magnetic powder consisting of particles of epsilon iron oxide in which some of the Fe sites have been substituted with other metal elements (substitutional epsilon iron oxide), the method comprising the steps of: a neutralization step of adding an alkali to a solution containing trivalent Fe ions and ions of a metal that partially substitutes the Fe sites to neutralize the solution to a pH of 2.0 to 5.0; a silicon oxide gel coating step of adding an alkali metal silicate to the neutralized solution obtained in the neutralization step to obtain a silicon oxide gel-coated iron oxyhydroxide in which some of the Fe sites have been substituted with other metal elements, or a mixture of iron oxyhydroxide and a hydroxide of the substitution element (hereinafter these will be referred to as substituted iron oxyhydroxide); and a water washing step of washing the silicon oxide gel-coated substituted iron oxyhydroxide obtained in the coating step with water to reduce the amount of alkali metal contained in the iron oxyhydroxide in which some of the Fe sites have been substituted with other metal elements. [2] In the method for producing an iron-based oxide magnetic powder described in [1] above, after the water-washing step, it is preferable to perform the water washing so that the substituted iron oxyhydroxide has a molar ratio A / (Fe+M) of 0.08 or less, where A moles is the amount of alkali metal contained in the substituted iron oxyhydroxide and Fe+M moles is the sum of the amounts of Fe and substituting metal element M contained in the substituted iron oxyhydroxide. [3] In the silicon oxide gel coating step described in the above item [1], an alkali may be further added to the reaction solution obtained after the addition of the alkali metal silicate to adjust the pH to 7.0 or more and 10.0 or less. [4] The other metal element partially substituting the Fe sites described in the above item [1] is preferably one or more selected from the group consisting of Co, Ti, Ga and Al. [5] The method for producing the iron-based oxide magnetic powder described in the above item [1] may further include a calcination step of calcining the silicon oxide gel-coated substituted iron oxyhydroxide obtained in the above water-washing step to obtain substituted epsilon-iron oxide coated with silicon oxide, and an oxide coating removal step of removing the silicon oxide from the silicon oxide-coated substituted epsilon-iron oxide obtained in the above calcination step to obtain the iron-based oxide magnetic powder. Effect of the Invention

[0008] As described above, by using the manufacturing method of the present invention, it is possible to provide a method for manufacturing iron-based oxide magnetic powder that can suppress the generation of the heterogeneous α phase, even when an alkali metal silicate is used as the silicon source. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a flow diagram showing an outline of a production method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Iron-based iron oxide magnetic powder] The manufacturing method of the present invention is for producing an iron-based oxide magnetic powder mainly containing ε-type oxides in which part of the Fe site of ε-Fe2O3 is replaced with other metal elements, and the magnetic powder contains a heterogeneous phase whose production is unavoidable during the manufacturing process. The heterogeneous phase is mainly α-type iron-based oxide, and the iron-based oxide magnetic powder obtained by the present invention is substantially composed of ε-type iron-based oxide magnetic particles and α-type iron-based oxide. By using the manufacturing method of the present invention, it is possible to obtain an iron-based iron oxide magnetic powder with a reduced content of the heterogeneous α-type iron-based oxide, even when an alkali metal silicate is used as a silicon source, which will be described later. Whether or not a partially substituted product in which part of the Fe site of ε-Fe2O3 is substituted with another metal element has an ε structure can be confirmed by X-ray diffraction (XRD), high energy electron diffraction (HEED), etc. In the present invention, the identification of ε-type and α-type iron-based oxides is performed by XRD. When applying iron-based oxide magnetic powder to a magnetic recording medium or a radio wave absorber, it is preferable to reduce the content ratio of heterogeneous phases in the iron-based oxide magnetic powder as much as possible. In the case of the iron-based oxide magnetic powder obtained by the production method of the present invention, specifically, the content rate of the α-phase by the Rietveld analysis of the X-ray diffraction method is preferably 6.5% or less. By manufacturing a radio wave absorber using the iron-based oxide magnetic powder obtained by the production method of the present invention as a radio wave absorbing material, excellent radio wave absorption characteristics are expected to be obtained.

[0011] Regarding some substitution products that can be manufactured by the manufacturing method of the present invention, the following are listed. General formula ε-C z Fe 2-z O3 (where C is one or more trivalent metal elements selected from In, Ga, Al, 0 < z < 1). General formula ε-A x B y Fe 2-x-y O3 (where A is one or more divalent metal elements selected from Co, Ni, Mn, Zn, B is one or more tetravalent metal elements selected from Ti, Sn, 0 < x < 1, 0 < y < 1). General formula ε-A x C z Fe 2-x-z O3 (where A is one or more divalent metal elements selected from Co, Ni, Mn, Zn, C is one or more trivalent metal elements selected from In, Ga, Al, 0 < x < 1, 0 < z < 1). General formula ε-B y C z Fe 2-y-z O3 (where B is one or more tetravalent metal elements selected from Ti, Sn, C is one or more trivalent metal elements selected from In, Ga, Al, 0 < y < 1, 0 < z < 1). General formula ε-A x B y C z Fe 2-x-y-zO3 (where A is one or more divalent metal elements selected from Co, Ni, Mn, Zn; B is one or more tetravalent metal elements selected from Ti, Sn; C is one or more trivalent metal elements selected from In, Ga, Al; 0 < x < 1, 0 < y < 1, 0 < z < 1).

[0012] Here, the type substituted only with the C element has the advantage that the coercive force of the magnetic particles can be arbitrarily controlled and it is easy to obtain the same space group as ε-Fe2O3, but it may be inferior in thermal stability. In particular, when Ga and Al are used as C, the thermal stability of the obtained iron-based oxide magnetic powder is somewhat inferior, so it is preferable to simultaneously substitute with the A and / or B elements. The three-element substitution type of A, B, and C has the best balance of the above-mentioned characteristics and is excellent in heat resistance, ease of obtaining a single phase, and controllability of coercive force. As the element substituting the Fe site, it is preferable to contain Ti or Co which has the effect of improving the heat resistance of the iron-based oxide magnetic powder. From the viewpoints of maintaining high thermal stability and the coercive force of the magnetic particles at room temperature, it is more preferable to simultaneously substitute with the two elements of Ti and Co. The three-element substitution type has the advantage that it is easy to obtain the same space group as ε-Fe2O3 in addition to thermal stability and coercive force control. Therefore, it is preferable that the element substituting the Fe site is one or more selected from Ti, Co, Ga, and Al, and more preferably Ti, Co, and Ga.

[0013] [Average particle diameter and BET specific surface area] In the present invention, the average particle diameter of the iron-based oxide magnetic powder obtained by the production method of the present invention is not particularly defined, but it is preferably fine enough for each particle to have a single magnetic domain structure. Usually, an average particle diameter measured by a transmission electron microscope of 10 nm or more and 40 nm or less can be obtained. Also, as the BET specific surface area, about 30 to 80 m 2 / g can be obtained.

[0014] [Production method] Hereinafter, the production method of the present invention will be described according to the flow chart shown in FIG. 1. [Starting materials and precursors] In the manufacturing method of the present invention, an acidic aqueous solution (hereinafter referred to as raw material solution) containing trivalent iron ions and metal ions of the metal element that will eventually replace the Fe site is used as the starting material for the iron-based oxide magnetic powder. If divalent Fe ions are used instead of trivalent Fe ions as the starting material, a mixture containing divalent iron hydrate oxides and magnetite as well as trivalent iron hydrate oxides is generated as a precipitate, and the shape of the iron-based oxide particles finally obtained varies, making it impossible to obtain an iron-based oxide magnetic powder with a reduced content of α-type iron-based oxides as in the present invention. As a source of these iron ions or metal ions of the replacement element, it is preferable to use water-soluble inorganic acid salts such as nitrates, sulfates, and chlorides in terms of ease of availability and cost. When these metal salts are dissolved in water, the metal ions are dissociated and the aqueous solution becomes acidic. In that case, the pH of the raw material solution is less than 2.0, depending on the concentration of trivalent iron ions, the concentration of the metal ions of the replacement metal element, and the anion species of the salt used. When an alkali is added to this acidic aqueous solution containing metal ions to neutralize it and raise the pH to 2.0 or higher, a mixture of iron oxyhydroxide and hydroxide of the substituting element, or iron oxyhydroxide in which part of the Fe site has been substituted with another metal element (hereinafter these are collectively referred to as substituted iron oxyhydroxide) begins to precipitate. In the manufacturing method of the present invention, these substituted iron oxyhydroxides are used as precursors of the substituted ε iron oxide magnetic powder. The total metal ion concentration in the raw material solution is not particularly specified in the present invention, but is preferably 0.01 mol / kg or more and 0.5 mol / kg or less. If it is less than 0.01 mol / kg, the amount of iron-based oxide magnetic powder obtained in one reaction is small, which is not economically preferable. If the total metal ion concentration exceeds 0.5 mol / kg, the reaction solution is likely to gel due to rapid precipitation of hydroxides, which is not preferable.

[0015] [Neutralization process] In the manufacturing method of the present invention, an alkali is added to the raw material solution and neutralized until the pH reaches 2.0 to 5.0, thereby obtaining a dispersion of substituted iron oxyhydroxide, i.e., a neutralized solution. The hydroxide of trivalent iron ions mainly consists of oxyhydroxide. The pH of the neutralized solution is set to 2.0 or higher in order to sufficiently precipitate substituted iron oxyhydroxide; if the pH is less than 2.0, the precipitation of substituted iron oxyhydroxide may be insufficient. The pH is set to 5.0 or lower in order to maintain good dispersibility of the precipitate of substituted iron oxyhydroxide produced, as described below. The alkali used for neutralization may be any of hydroxides of alkali metals or alkaline earth metals, aqueous ammonia, and ammonium salts such as ammonium hydrogen carbonate, but it is preferable to use aqueous ammonia or ammonium hydrogen carbonate, which are less likely to leave impurities when finally heat-treated to form an ε-type iron-based oxide. These alkalis may be added in the form of a solid to the aqueous solution of the starting material, but from the viewpoint of ensuring the uniformity of the reaction, it is preferable to add them in the form of an aqueous solution. As described above, when an alkali is added to the raw material solution to carry out neutralization treatment, a precipitate of substituted iron oxyhydroxide is formed, and therefore, during the neutralization treatment, the dispersion containing the precipitate is stirred by a known mechanical means. The addition of the alkali to the raw material solution may be carried out continuously or intermittently from the start to the end of the addition. In the production method of the present invention, the reaction temperature during the neutralization treatment is not particularly limited, but the neutralization treatment can be carried out at room temperature. In order to accelerate the neutralization reaction, the reaction system may be heated, but in that case, the temperature should be 60° C. or lower. The pH values ​​described in this specification are values ​​measured using a glass electrode based on JIS Z8802, and refer to values ​​measured using a pH meter calibrated with an appropriate buffer solution according to the pH range to be measured as the pH standard solution. The pH values ​​described in this specification are values ​​directly read from the pH meter compensated by a temperature compensation electrode under reaction temperature conditions.

[0016] [Alkali metal silicates] The substituted iron oxyhydroxide, which is the precursor of the iron-based oxide magnetic powder produced in the above process, is unlikely to undergo a phase change to an ε-type iron-based oxide even if it is subjected to a heat treatment in its original state. Therefore, it is necessary to cover the substituted iron oxyhydroxide with silicon oxide prior to the heat treatment and then perform the heat treatment in a restrained state. In the production method of the present invention, an alkali metal silicate is used as a silicon source for coating the substituted iron oxyhydroxide with silicon oxide. Alkali metal silicates are substances with the general formula A2O xSiO2 yH2O (A is an alkali metal, x>0, y>0), and include sodium silicate, potassium silicate, lithium silicate, etc. These silicates are typically metasilicates such as Na2SiO3, K2SiO3, and Li2SiO3, but there are also substances with different degrees of polymerization and hydration, and they are sometimes supplied industrially in the form of an aqueous solution.

[0017] [Silicon oxide gel coating process] By adding an alkali metal silicate to the neutralized solution whose pH is between 2.0 and 5.0, a gel-like silicon oxide is deposited on the surface of the substituted iron oxyhydroxide. In this case, the alkali metal silicate dissociates in the aqueous solution to form silicate ions, and it is believed that the hydroxide of the silicate ions becomes gel-like and deposits. When the alkali metal silicate is added within the above pH range, the content of α-phase in the finally obtained substituted ε-iron oxide is reduced, and the particle size distribution of the iron-based oxide magnetic powder is narrowed. The mechanism is not clear at present, but the inventors speculate as follows. At the stage where an alkali is added to the raw solution to a pH range of 2.0 to 5.0, the nucleated substituted iron oxyhydroxide particles are in the process of growing, and since their particle size is small, they are considered to show good dispersibility in the neutralized solution. By adding an alkali metal silicate to the neutralized solution at this stage, it is considered that an iron oxyhydroxide coated with silicon oxide gel having a narrow particle size distribution is obtained, and the particle size distribution of the iron oxide magnetic powder becomes narrow, and as a result, the content of α-phase in the finally obtained substituted ε-iron oxide is reduced. If the pH exceeds 5.0, the dispersibility of the substituted iron oxyhydroxide particles is deteriorated, and the amount of α-phase in the resulting substituted ε-iron oxide magnetic powder is considered to increase. In addition, since alkali metal silicates are themselves strong alkalis, when they are added to the neutralized liquid, the pH of the reaction system rises, and the iron oxyhydroxide coated with silicon oxide gel continues to grow, increasing its particle size. The alkali metal silicate is preferably added in the form of an aqueous solution in order to ensure uniformity of adhesion to the substituted iron oxyhydroxide and to facilitate separation of the alkali metal from the silicon oxide gel-coated substituted iron oxyhydroxide in the water washing step described below. In the present invention, the temperature at which the alkali metal silicate is added is not particularly specified, but it can be added at room temperature. The reaction system may be heated to accelerate the adhesion reaction, but in that case, the temperature should be 60°C or lower.

[0018] The amount of alkali metal silicate added is preferably such that S / (F+M) is 0.50 or more and 10.0 or less, where S is the number of moles of silicon added, F is the number of moles of Fe ions contained in the raw material solution, and M is the total number of moles of substituted metal element ions. If S / (F+M) is less than 0.50, the amount of silicon oxide coating on the surface of the precipitate of substituted iron oxyhydroxide decreases, which is undesirable because it makes it easier for α-type iron oxide to be generated. Also, if S / (F+M) exceeds 10.0, the amount of processing in the heating step and the silicon oxide removal step described below increases, which is undesirable because it increases the production cost. After adding the alkali metal silicate to the alkali-added liquid, the mixture is stirred for a predetermined period of time to mature the gel-like coating on the surface of the substituted iron oxyhydroxide. The above-mentioned holding time may be set to 3 to 24 hours, taking into consideration the pH and temperature of the alkali-added liquid.

[0019] The amount of alkali metal silicate added is determined by the above conditions, but from the viewpoint of effectively utilizing the trivalent iron ions and metal ions of the replacing metal element contained in the raw material solution, it is preferable to set the pH of the reaction solution after the addition of the alkali metal silicate to 7.0 or more and 10.0 or less. When the pH of the reaction solution after the addition of the alkali metal silicate is less than 7.0, the pH can be set to 7.0 or more and 10.0 or less by adding further alkali to the reaction solution. In addition, the reaction solution to which the alkali has been added can be held for a predetermined period of time.

[0020] [Washing process] In the method for producing the iron-based oxide magnetic powder of the present invention, a water washing step is provided following the silicon oxide gel coating step. The water washing can be performed by a known method, for example, a method in which water is passed through the solid obtained by filtering the slurry obtained in the silicon oxide gel coating step using a Buchner funnel, or a method by cross-flow filtration using an ultrafiltration membrane. The washing is preferably performed so that the molar ratio A / (Fe+M) is 0.08 or less, and more preferably so that the molar ratio A / (Fe+M) is 0.06 or less, where A mole is the amount of alkali metal contained in the substituted iron oxyhydroxide in the silicon oxide gel-coated substituted iron oxyhydroxide obtained in the above step, and Fe+M mole is the sum of the amounts of Fe and the substituted metal element M contained in the substituted iron oxyhydroxide. When A / (Fe+M) is 0.08 or less, an iron-based iron oxide magnetic powder having an α-phase content of 6.5 mass% or less can be finally obtained. The alkali metal contained in the substituted iron oxyhydroxide is, for example, one or more selected from Na, K, and Li. For example, when the alkali metal is Na, the above molar ratio can be expressed as Na / (Fe+M). At present, the reason why the α-phase content decreases when A / (Fe+M) is set to 0.08 or less is unclear, but the inventors presume as follows. That is, it is believed that the alkali metal contained in the substituted iron oxyhydroxide becomes an oxide of the alkali metal in the heating step described below, and that this alkali metal oxide acts as a sintering aid for the iron-based oxide. Therefore, it is believed that if the amount of alkali metal contained in the substituted iron oxyhydroxide increases, the particle size of the iron-based oxide after heating increases and becomes coarse particles, and as a result, it becomes easier for the α-phase, which is a thermodynamically stable phase, to form. If the alkali metal silicate is added in the silicon oxide gel coating step when the pH of the reaction solution is 7.0 or higher, the effect of reducing the α-phase content is reduced even if A / (Fe+M) is set to 0.08 or lower. The reason why the amount of alkali metal in the substituted iron oxyhydroxide contained therein decreases when the silicon oxide gel-coated substituted iron oxyhydroxide is washed away with the wash water is believed to be that after the added alkali metal silicate is adhered to the surface of the substituted iron oxyhydroxide as silicon oxide, the alkali metal (ions) remaining on the surface of the substituted iron oxyhydroxide coated with silicon oxide gel and in the gaps in the adhered silicon oxide gel are washed away with the wash water. Since the above measurement of A / (Fe+M) is a destructive analysis, it is necessary to understand the relationship between the silicon oxide gel coating conditions and the water washing conditions in the production of iron-based oxide magnetic powder. In a simple way, the value of A / (Fe+M) can be estimated by measuring the electrical conductivity of the filtrate after the above filtration, and A / (Fe+M) can be reduced to 0.08 or less by washing with water until the electrical conductivity is 1000 mS / m or less.

[0021] In the method for producing the iron-based oxide magnetic powder of the present invention, the steps after the aging step can be the same as those in the conventional production methods described in, for example, Patent Documents 1 to 4. Specifically, the following steps can be mentioned. [Heating process] In the manufacturing method of the present invention, the silicon oxide gel-coated substituted iron oxyhydroxide with reduced alkali metal content in the substituted iron oxyhydroxide is recovered by a known solid-liquid separation method, and then heat-treated to obtain ε-type iron-based oxide magnetic powder. Before the heat treatment, a washing and drying step may be performed. The heat treatment is performed in an oxidizing atmosphere, which may be air. The heating can be performed at a temperature in the range of about 700°C to 1300°C, but since a high heating temperature tends to produce α-Fe2O3 (a different phase from ε-Fe2O3), which is a thermodynamically stable phase, the heat treatment is preferably performed at a temperature in the range of 900°C to 1200°C, more preferably 950°C to 1150°C. The heat treatment time can be adjusted within a range of 0.5 to 10 hours, but good results are likely to be obtained within a range of 2 to 5 hours. [Oxide coating removal process] When the iron-based oxide magnetic powder does not require a coating of silicon oxide, the silicon oxide coating may be removed after the heat treatment. As a specific method, since silicon oxide is soluble in an alkaline aqueous solution, the iron oxide magnetic powder coated with silicon oxide after heat treatment can be dissolved and removed by immersing it in an aqueous solution containing a strong alkali such as NaOH or KOH and stirring it. To increase the dissolution rate, it is recommended to heat the alkaline aqueous solution. Typically, silicon oxide can be dissolved well by adding an alkali such as NaOH in an amount three times the molar amount of silicon oxide or more and stirring the slurry containing the powder at an aqueous solution temperature of 60°C to 90°C.

[0022] [Evaluation of crystallinity by X-ray diffraction (XRD)] The obtained sample was subjected to powder X-ray diffraction (XRD: Rigaku Corporation, sample horizontal type multipurpose X-ray diffractometer Ultima IV, radiation source CuKα radiation, voltage 40 kV, current 40 mA, 2θ = 10° to 70°). The obtained diffraction pattern was evaluated by Rietveld analysis using integrated powder X-ray analysis software (PDXL2: Rigaku Corporation) based on ICSD (inorganic crystal structure database) No. 173025: Iron (III) Oxide-Epsilon, No. 82134: Hematite, to confirm the crystal structure and the content of α phase.

[0023] [Magnetic hysteresis curve (BH curve) measurement] The magnetic properties of the obtained substituted ε iron oxide magnetic powder were measured under the following conditions. The magnetic properties were measured using a vibrating sample magnetometer (VSM) (VSM-5 manufactured by Toei Kogyo Co., Ltd.). The applied magnetic field was 1193 kA / m (15 kOe) and the M measurement range was 0.005 A m 2 The magnetic properties were measured with a magnetic field change rate of 15 (kA / m s), a time constant of 0.03 seconds, and a wait time of 0.1 seconds. The attached software (Ver. 2.1) made by Toei Kogyo Co., Ltd. was used for this measurement.

[0024] [Chemical composition of iron oxide magnetic powder] The composition analysis of the substituted ε-iron oxide magnetic powder and the iron oxide magnetic powder coated with silicon oxide was performed using an Agilent Technologies ICP-720ES, with the measurement wavelengths (nm) being Fe; 259.940 nm, Ga; 294.363 nm, Co; 230.786 nm, Ti; 336.122 nm, Al; 396.152 nm, and Si; 288.158 nm. The method for analyzing alkali metals in iron oxide magnetic powder coated with silicon oxide is as follows. After placing 1 g of sample in a PTFE beaker, 10 ml of ultrapure water, 10 ml of 35% HCl aqueous solution, and 0.5 ml of 46% hydrofluoric acid aqueous solution were added and heated to dissolve. Heating was continued to dry the sample, and the sample was allowed to cool. 10 ml of ultrapure water and 10 ml of 35% HCl aqueous solution were added, heated to dissolve the sample, and the sample was allowed to dry again and cooled. Further, 10 ml of ultrapure water and 5 ml of 35% HCl aqueous solution were added, heated to dissolve the sample, allowed to cool, transferred to a 100 ml measuring flask, and the volume was determined. The concentration of alkali metals was measured by atomic absorption spectrometry using a Hitachi High-Tech Science ZA3300 to calculate the amount of dissolved alkali metals, and the dissolved amount was divided by the mass of the sample to calculate the mass-based content of alkali metals contained in the sample.

[0025] [BET specific surface area] The BET specific surface area was determined by the BET single point method using a Macsorb model-1210 manufactured by Mountech Corporation. EXAMPLES

[0026] [Example 1] In a 1L reaction tank, 102.75g of ferric sulfate (III) solution with an Fe concentration of 11.65 mass%, 14.04g of Ga(III) nitrate solution with a Ga concentration of 11.55 mass%, 1.88g of cobalt (II) nitrate hexahydrate with a purity of 97%, and 1.98g of titanium (IV) sulfate with a Ti concentration of 15.1 mass% were dissolved in 738.54g of pure water while mechanically stirring with a stirring blade in an air atmosphere to obtain a raw material solution (Step 1). The pH of this raw material solution was about 1. The molar ratio of metal ions in this raw material solution was Fe:Ga:Co:Ti=1.714:0.186:0.050:0.050. The Roman numerals in parentheses after the names of the reagents indicate the valence of the metal elements. In an air atmosphere, this raw material solution was mechanically stirred with a stirring blade under the condition of 30° C., while 50.63 g of a 22.14 mass % aqueous ammonia solution was added over 10 minutes (Procedure 2). The pH of the reaction solution (neutralized solution) at the end of the addition of the aqueous ammonia solution was 3.0. Thirty minutes after the addition of the aqueous ammonia solution, 145.15 g of an aqueous sodium silicate solution (No. 5 sodium silicate solution manufactured by Fuji Chemical Co., Ltd.) with a Si concentration of 12.10 mass% and a Na concentration of 5.27 mass% was added dropwise over 10 minutes. After the entire aqueous sodium silicate solution was added, stirring was continued for 20 hours, and the precipitate of iron oxyhydroxide containing substitution elements was covered with silicon oxide gel (step 3). The pH of the reaction solution after the addition of the aqueous sodium silicate solution and throughout the 20 hours of stirring was 9.0. Note that under these conditions, the molar ratio S / (F+M) of the total amount of Si element contained in the No. 5 aqueous sodium silicate solution to be added dropwise to the dispersion liquid to the amount of iron, gallium, cobalt, and titanium ions contained in the raw solution was 2.5. The slurry obtained in step 3 was filtered using a Buchner funnel, and the solids obtained were washed with pure water until the electrical conductivity of the filtrate after the water passage was 20 mS / m or less, thereby obtaining a cake of silicon oxide gel-coated substituted iron oxyhydroxide after water washing. Here, the water washing was performed by passing 2 kg of pure water through the filter and discarding it, then passing 0.2 kg of pure water through the filter and measuring the electrical conductivity of the liquid after the water passage, and then repeating the passing of 0.2 kg of pure water through the filter and measuring the electrical conductivity until the electrical conductivity was 20 mS / m or less. The obtained cake was dried at 110°C in air (step 4). A composition analysis was performed on the dried product obtained in step 4, and the Na / (Fe+M) molar ratio was 0.052. The dried product obtained in step 4 was heated in air at 1000°C for 4 hours in a box-type sintering furnace to obtain iron-based oxide magnetic powder coated with silicon oxide (step 5). Note that the silicon oxide gel is dehydrated and converted to oxide when heat-treated in air. The production conditions of this example, such as the conditions for preparing the raw material solution, are shown in Table 1. Table 1 also shows the production conditions of other examples and comparative examples.

[0027] The heat-treated powder, obtained by heat-treating the dried product of the silicon oxide gel-coated substituted iron oxyhydroxide obtained in step 5, was stirred in a 20 mass% NaOH aqueous solution at about 60°C for 24 hours to remove the silicon oxide coating from the particle surface (step 6). Next, the slurry obtained in step 6 was subjected to solid-liquid separation by centrifugation, and the obtained solid matter was washed with water and dried, and the obtained substituted ε iron oxide magnetic powder was subjected to chemical analysis of the composition, XRD measurement, measurement of magnetic properties, etc. The measurement results are shown in Table 2. Table 2 also shows the physical property values ​​of the substituted ε iron oxide magnetic powder obtained in other examples and comparative examples.

[0028] [Example 2] In step 1 of Example 1, a raw material solution was prepared using 738.54 g of pure water, 92.32 g of ferric sulfate (III) solution with an Fe concentration of 11.65 mass%, 64.78 g of Al (III) sulfate solution with an Al concentration of 1.88 mass%, 1.88 g of cobalt (II) nitrate hexahydrate with a purity of 97%, and 1.98 g of titanium (IV) sulfate with a Ti concentration of 15.1 mass%, and the heat treatment temperature was set to 1040°C. Except for this, a substituted ε iron oxide magnetic powder was obtained in the same manner as in Example 1. The obtained substituted ε iron oxide magnetic powder was subjected to chemical analysis of the composition, XRD measurement, and measurement of magnetic properties. The molar ratio of metal ions in the raw material solution was Fe:Al:Co:Ti=1.54:0.36:0.050:0.050. The pH of the reaction solution was 3.0 at the end of the addition of the aqueous ammonia solution, and was 9.0 after the addition of the aqueous sodium silicate solution and throughout the 20-hour stirring period. A composition analysis was carried out on the dried product obtained in step 4, and the Na / (Fe+M) molar ratio was found to be 0.064.

[0029] [Example 3] In Example 2, the amounts of the ferric sulfate (III) solution, Al (III) sulfate solution, cobalt (II) nitrate hexahydrate, and titanium (IV) sulfate were changed so that the molar ratio of metal ions in the raw solution was Fe:Al:Co:Ti = 1.48:0.45:0.035:0.035, the amount of the aqueous sodium silicate solution was changed so that S / (F+M) was 1.5, and after the aqueous sodium silicate solution was added, 22.14 mass% aqueous ammonia solution was added until the pH of the reaction solution became 9.0, and then stirring was performed for 20 hours. A substituted ε iron oxide magnetic powder was obtained by the same procedure as in Example 2. The pH of the reaction solution at the time when the addition of the aqueous ammonia solution was completed in Step 2 was 3.0. The obtained substituted ε iron oxide magnetic powder was subjected to chemical analysis of the composition, XRD measurement, measurement of magnetic properties, etc. A composition analysis was performed on the dried product obtained in Step 4, and the Na / (Fe+M) molar ratio was 0.036.

[0030] [Example 4] Substituted ε iron oxide magnetic powder was obtained by the same procedure as in Example 3, except that a Co(II) sulfate solution with a Co concentration of 5.01 mass% was used instead of cobalt(II) nitrate hexahydrate, and a titanium(IV) tetrachloride solution with a Ti concentration of 16.9 mass% was used instead of titanium(IV) sulfate. The molar ratio of metal ions in the raw solution was Fe:Al:Co:Ti=1.48:0.45:0.035:0.035. The pH of the reaction solution at the time when the addition of the ammonia aqueous solution in step 2 was completed was 3.0. The obtained substituted ε iron oxide magnetic powder was subjected to chemical analysis of the composition, XRD measurement, and measurement of magnetic properties. When the composition analysis was performed on the dried product obtained in step 4, the Na / (Fe+M) molar ratio was 0.026.

[0031] [Comparative Example 1] In a 5L reaction tank, 513.77g of ferric sulfate (III) solution with an Fe concentration of 11.65% by mass, 86.54g of Ga(III) nitrate solution with a Ga concentration of 9.37% by mass, 9.38g of cobalt(II) nitrate hexahydrate with a purity of 97%, and 9.91g of titanium(IV) sulfate with a Ti concentration of 15.1% by mass were dissolved in 3482.14g of pure water while mechanically stirring with a stirring blade in an air atmosphere to obtain a raw solution (Procedure 1). The pH of this raw solution was about 1. The molar ratio of metal ions in this raw solution was Fe:Ga:Co:Ti=1.714:0.186:0.050:0.050. The Roman numerals in parentheses after the names of the reagents indicate the valence of the metal elements. In an air atmosphere, this raw material solution was mechanically stirred with a stirring blade at 30° C., while 407.83 g of a 21.24 mass % aqueous ammonia solution was added over 10 minutes (Procedure 2). The pH of the reaction solution at the end of the addition of the aqueous ammonia solution was 8.7. Thirty minutes after the addition of the aqueous ammonia solution, 725.77 g of an aqueous sodium silicate solution (No. 5 sodium silicate solution manufactured by Fuji Chemical Co., Ltd.) with a Si concentration of 12.10 mass% and a Na concentration of 5.27 mass% was added dropwise over 10 minutes. After the entire aqueous sodium silicate solution was added, stirring was continued for 20 hours, and the precipitate of iron oxyhydroxide containing substitution elements was covered with silicon oxide gel (step 3). The pH of the reaction solution after the addition of the aqueous sodium silicate solution and throughout the 20 hours of stirring was 11. Note that under these conditions, the molar ratio S / (F+M) of the total amount of Si element contained in the No. 5 aqueous sodium silicate solution to be added dropwise to the dispersion liquid to the amount of iron, gallium, cobalt, and titanium ions contained in the raw solution was 2.5. The slurry obtained in step 3 was filtered, and the moisture of the resulting precipitate of silicon oxide gel-coated substituted iron oxyhydroxide was removed as much as possible, and the resulting cake was then dried in air at 110°C to obtain a dried product of silicon oxide gel-coated substituted iron oxyhydroxide (step 4). A composition analysis was carried out on the dried product obtained in step 4, and the Na / (Fe+M) molar ratio was found to be 0.259. The dried product obtained in step 4 was heat-treated in air at 1000° C. for 4 hours in a box-type sintering furnace to obtain iron-based oxide magnetic powder coated with silicon oxide (step 5).

[0032] The heat-treated powder obtained by heat-treating the dried product of the silicon oxide gel-coated substituted iron oxyhydroxide obtained in step 5 was stirred in a 17.58 mass% NaOH aqueous solution at about 60°C for 24 hours to remove the silicon oxide coating from the particle surface (step 6). Next, the slurry obtained in step 6 was subjected to solid-liquid separation by centrifugation, and the obtained solid was washed with water and dried, and the composition of the obtained substituted ε-iron oxide magnetic powder was subjected to chemical analysis, XRD measurement, measurement of magnetic properties, etc.

[0033] [Comparative Example 2] A substituted ε iron oxide magnetic powder was obtained by the same procedure as in Example 1, except that in step 2 of Example 1, a 22.14 mass % ammonia aqueous solution was added at an addition rate of 8.02 g / min until the pH of the reaction solution reached 8.6. The obtained substituted ε iron oxide magnetic powder was subjected to chemical analysis of the composition, XRD measurement, measurement of magnetic properties, etc. When a composition analysis was carried out on the dried product obtained in step 4, the Na / (Fe+M) molar ratio was 0.049.

[0034] [Table 1]

[0035] [Table 2]

Claims

1. A method for producing an iron-based oxide magnetic powder made of ε-iron oxide particles in which a part of the Fe site is replaced with another metal element, comprising the steps of: a neutralization step of adding an alkali to a solution containing trivalent Fe ions and ions of a metal that partially substitutes the Fe sites to neutralize the solution to a pH of 2.0 or more and 5.0 or less; a silicon oxide gel coating step of adding an alkali metal silicate to the neutralized solution obtained in the neutralization step to obtain an iron oxyhydroxide in which a part of the Fe site coated with silicon oxide gel is substituted with another metal element, or a mixture of iron oxyhydroxide and a hydroxide of the substituted element (hereinafter, these are referred to as substituted iron oxyhydroxide); a water washing step in which the silicon oxide gel-coated substituted iron oxyhydroxide obtained in the coating step is washed with water to reduce the amount of alkali metals contained in the iron oxyhydroxide in which a portion of the Fe sites has been substituted with other metal elements; a calcination step of calcining the substituted iron oxyhydroxide coated with silicon oxide gel obtained in the water washing step to obtain iron oxide containing a substituted metal element coated with silicon oxide; an oxide coating removal step of removing the silicon oxide from the iron oxide containing the substitution metal element coated with silicon oxide obtained in the firing step to obtain an iron-based oxide magnetic powder; A method for producing an iron-based oxide magnetic powder, comprising:

2. 2. The method for producing an iron-based oxide magnetic powder according to claim 1, wherein after the water-washing step, the water-washing is performed so that the substituted iron oxyhydroxide has a molar ratio A / (Fe+M) of 0.08 or less, where A moles is the amount of alkali metal contained in the substituted iron oxyhydroxide and Fe+M moles is the sum of the amounts of Fe and substituting metal element M contained in the substituted iron oxyhydroxide.

3. 2. The method for producing iron-based oxide magnetic powder according to claim 1, wherein in the silicon oxide gel coating step, an alkali is further added to the reaction solution obtained after adding the alkali metal silicate to adjust the pH to 7.0 or more and 10.0 or less.

4. 2. The method for producing an iron-based oxide magnetic powder according to claim 1, wherein the other metal element partially substituting the Fe site is at least one selected from the group consisting of Co, Ti, Ga and Al.

Citation Information

Patent Citations

  • METHOD FOR PRODUCING epsilon-Fe2O3 CRYSTAL

    JP2008174405A

  • Precursor of iron-based oxide magnetic particle powder and method for producing iron-based oxide magnetic particle powder using the same

    JP2016098131A

  • Ferrous oxide magnetic particle powder, method for manufacturing the same, coating material, and magnetic recording medium

    JP2016130208A

  • Ε iron oxide powder with part of iron sites substituted with metal element other than iron, method of producing the same, and paste

    JP2018172227A

  • Substitution-type ε-iron oxide magnetic particle powder, method for producing substitution-type ε-iron oxide magnetic particle powder, green compact, method for producing green compact, and electromagnetic wave absorber

    JP2020167365A